Synthesis of protected precursors of chitin oligosaccharides by electrochemical polyglycosylation of thioglycosides - Rahman, Md Azadur; Kuroda, Kana; Endo, Hirofumi; Sasaki, Norihiko; Hamada, Tomoaki; Sakai, Hiraku; Nokami, Toshiki (Beilstein journal of organic chemistry, 2022)
The synthesis of protected precursors of chitin oligosaccharides by electrochemical polyglycosylation of thioglycosides as monomer is described. Oligosaccharides up to the hexasaccharide were synthesized under optimized reaction conditions. Further, a modified method enabled the synthesis of oligosaccharides up to the octasaccharide by repeating electrolysis with additional monomers. The mechanism of the electrochemical polyglycosylation is also discussed, based on the oxidation potential of the monomer and oligosaccharides.